Development of Molecool game in instagram for chemistry Mol concept fun learning / Mohamad Idris Saidin and Fatin Hamimi Mohd Fazly - Saidin, Mohamad Idris; Mohd Fazly, Fatin Hamimi (Universiti Teknologi MARA, Negeri Sembilan, 2023)
This study aims to develop the Molecool game in the Instagram application for a fun learning of the chemistry mole concept. The objective of the study is to determine the validity and identify the usability of the Molecool game from the constructs of usefulness, satisfaction, and ease. The study design is a developmental study that adapts the instructional design of the ADDIE model. The study population is among chemistry trainee teachers from Universiti Pendidikan Sultan Idris. A total of 107 respondents were selected through a simple sampling technique. A descriptive statistical analysis was employed in this study. The research instrument consists of a content validity form, questionnaire validity as well as a Molecool game usability questionnaire. The findings of the study were analyzed using SPSS software version 27.0.0.0 by observing at the values of frequency, percentage, mean and standard deviation. The results of the study show that the Molecool game has a good level of content validity through the percentage of expert agreement that exceeds 70%. The research findings for the three constructs in the usability questionnaire obtained a good mean value of 3.74 (sd = 0.397) for usefulness, 3.74 (sd = 0.387) for satisfaction and ease of use was 3.74 (sd = 0.397). This shows that the Molecool game has a good level of usability. The implication is that the Molecool game has the potential to be used as a teaching aid as well as a reinforcement activity for students in learning the standard content of the mole concept.